Lateralized modulation of beta-band power in sensorimotor areas during action observation - Lange, Joachim; Pavlidou, Anastasia; Schnitzler, Alfons (Frontiers in Integrative Neuroscience, 2015)
The cortical network for action observation includes areas of the visual cortex and non-visual areas, including areas of the motoric system. Parts of this network are known for their contralateral organization during motion execution, i.e. they predominantly control and respond to movements of the contralateral body side. We were interested whether this lateralized organization was also present during action observation. Human participants viewed point-light displays of human actors, where the actor was facing and moving either to the right or to the left, while participants' neuromagnetic activity was recorded using magnetoencephalography (MEG). We found that right and left facing movements elicited different activity in left and right motoric areas. This lateralization effect was found in two distinct spatio-temporal-spectral clusters: An early lateralization effect in medial sensors at 12-16 Hz and ~276-675 ms after stimulus onset, and a second cluster in more lateral sensors at 22-28 Hz and ~1275-1775 ms. Our results demonstrate that in addition to the known somatotopic organization of parts of the human motoric system, these areas also show a lateralization effect during action observation. Thus, our results indicate that the hemispheric organization of one's own body map known for motion execution extends to the visual observation of others’ bodily actions and movements.